2019
DOI: 10.12659/msm.912774
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Montelukast on Bronchopulmonary Dysplasia (BPD) and Related Mechanisms

Abstract: BackgroundBronchopulmonary dysplasia (BPD) is a chronic lung disease common in preterm infants. Montelukast, an effective cysteinyl leukotriene (cysLT) receptor antagonist, has a variety of pharmacological effects and has protective effects against a variety of diseases. Currently, the efficacy and safety of montelukast sodium in treating BPD has been revealed, however, the precise molecular mechanism of the effect of montelukast on BPD development remain largely unclear. Therefore, this study aimed to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 30 publications
5
32
0
Order By: Relevance
“…Then, leukocytes accumulating in the lungs are activated and secretive reactive oxygen species and proteases that damage capillary endothelium and alveolar epithelium. Montelukast therapy has been shown in recent studies to reduce TNF-α, IL-6 and IL-1b levels [3,4]. The pronounced inhibitory effect of montelukast against bradykinin-induced tracheal smooth muscle contraction has also been demonstrated, which supports the interaction between bradykinin and leukotriene mediators [3,6].…”
Section: To the Editormentioning
confidence: 90%
See 1 more Smart Citation
“…Then, leukocytes accumulating in the lungs are activated and secretive reactive oxygen species and proteases that damage capillary endothelium and alveolar epithelium. Montelukast therapy has been shown in recent studies to reduce TNF-α, IL-6 and IL-1b levels [3,4]. The pronounced inhibitory effect of montelukast against bradykinin-induced tracheal smooth muscle contraction has also been demonstrated, which supports the interaction between bradykinin and leukotriene mediators [3,6].…”
Section: To the Editormentioning
confidence: 90%
“…In addition, as it is known, COVID-19 reaches the cell through angiotensin-converting enzyme (ACE) receptors and leads to severe pneumonia and thus increased mortality rates during infection by binding to human ACE2 [3,4]. The cough that can develop with ACE inhibition is caused by increased bradykinin and its bronchoconstrictor effect, and montelukast, a selective LTD4 antagonist, has an inhibitory effect on bradykinin-induced airway hypersensitivity [5,6].…”
Section: To the Editormentioning
confidence: 99%
“…It is claimed that montelukast, a potent cysteinyl leukotriene receptor antagonist, can be a potential therapeutic agent in COVID -19 [29]. Montelukast suppresses leukotrienemediated inflammatory response by inhibiting the binding of leukotrienes to the receptor [30]. The most important cause of COVID -19 related deaths is ARDS.…”
Section: Wisniacki Et Al Administered Tweak -Blocking Monoclonal Antmentioning
confidence: 99%
“…These activated leukocytes then secrete proteases and reactive oxygen species (ROS) that lead to capillary and alveolar damage, which is responsible for the leaky capillaries [31]. Treatment with montelukast has found to decrease these afore mentioned inflammatory cytokines and markers of oxidative stress like malondialdehyde (MDA) in some animal models [32].…”
Section: Mechanism Of Action Of Montelukastmentioning
confidence: 99%
“…Montelukast use blocks all the above activities [61]. Recent studies have shown that Montelukast can lower elevated levels of IL-1b, IL-6, IL-8, TNF-Alpha [32,38]. Montelukast also demonstrated a prominent inhibitory effect on bradykinin mediated tracheal smooth muscle contraction, which could be related to leukotriene interaction [40].…”
Section: Montelukast For Covid-19 Infectionmentioning
confidence: 99%